2016
DOI: 10.1021/acs.jpcb.6b00684
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of Hydrophobic Gating, Knock-on Effect, and Ion Binding Determines Ion Selectivity in the p7 Channel

Abstract: Ion channels selectively allow certain ions to pass through at much higher rates than others, and thereby modulate ionic concentrations across cell membranes. The current molecular dynamics study elucidates the intricate mechanisms that render ion selectivity to the viral channel p7 by employing free energy calculations. Free energy barriers of 5.4 and 19.4 kcal mol(-1) for K(+) and Ca(2+), respectively, explain the selectivity of the channel reported in experiments. Initially, the permeating ions encounter a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In this configuration, the NH 2 groups of the two molecules are close together (visual inspection), so that there is electrostatic repulsion between them. This repulsion drives the transition from intermediate III to intermediate IV, and such repulsion is reminiscent of the knock-on phenomenon seen in ion transport. , There is an alternative path that could be followed to reach intermediate IV, that via intermediate IIb. In this path, however, there is a complete absence of interurea knock-on, and there is no force to drive the first urea molecule out of the selectivity filter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this configuration, the NH 2 groups of the two molecules are close together (visual inspection), so that there is electrostatic repulsion between them. This repulsion drives the transition from intermediate III to intermediate IV, and such repulsion is reminiscent of the knock-on phenomenon seen in ion transport. , There is an alternative path that could be followed to reach intermediate IV, that via intermediate IIb. In this path, however, there is a complete absence of interurea knock-on, and there is no force to drive the first urea molecule out of the selectivity filter.…”
Section: Resultsmentioning
confidence: 99%
“…The windows sampled include all configurations intermediate between the two urea molecules entering the pore from the periplasmic side, and the two molecules exiting from the cytoplasmic side. The minimum free energy path (MFEP) was calculated using an approach described previously, 26 and snapshots corresponding to important intermediates in the transport process are shown above and below the free energy landscape in the figure. Five stable configurations are identified from the free energy surface, and these are labeled I, IIa, IIb, III, and IV.…”
Section: Journal Of Chemical Theory and Computationmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamics (MD) simulations have served as an indispensable technique in characterizing ion transport through biological channels. Early MD studies on the KcsA K + channel revealed that ion conduction through the channel is facilitated by a knock-on mechanism, whereby the movement of an ion through the channel is propelled by electrostatic repulsion from a subsequent ion entering the channel . It was later shown that the knock-on event involves fully desolvated ions .…”
Section: Introductionmentioning
confidence: 99%